Design and analysis of mesh size subjected to wheel rim convergence using finite element method - Sanjaya, Yuwana (2021)
This paper discusses the effect of meshing size on wheel rim. It is not known that every design needs to consider the optimum result of the design, in reality the simulation cannot generates the optimal analysis due to several factors. One of the influencing factors in the simulation is the mesh size when simulating the wheel rim design. It is known that each mesh size gives different results, therefore it is necessary to do a calibration using finite element method from the benchmarking literature studies that have discussed this case before. Authors designed a vehicle wheel using Fusion360 and ran the simulating static analysis using ANSYS. The material used is steel and the boundary conditions of its design is angular velocity and load. The wheel designs were given different mesh sizes and resulted in stress (von-Mises) and displacement, since the results were analyzed for mesh convergence. For the convergence result, wheel rim has a von-Mises stress for 10 mm, 15 mm, and 20 mm size mesh is 164.38 MPa, 128.68 MPa, and 131.08 MPa, and the displacement is 0.16117 mm, 0.15592 mm, 0.15286 mm. The simulation made stress ratio for 1.174, 0.919, 0.936 and displacement ratio for 0.989, 0.957, 0.938. Through the use of different mesh sizes, different results can be proven, this is necessary to determine the convergence of the mesh used in the simulation. This paper proves that 10, 15, 20 mm size mesh convergence, with error ratio of displacement is 0.011, 0.043, 0.062 and the error ratio of stress is -0.174, 0.081, 0.064 to the benchmarking studies literature.